2019
DOI: 10.3389/fmicb.2019.02424
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic Proteins Interact With Intracellular Melatonin in Saccharomyces cerevisiae

Abstract: Melatonin is a bioactive compound that is present in fermented beverages and synthesized by yeast during alcoholic fermentation. Many studies have shown that melatonin interacts with some mammalian proteins, such as sirtuins or orphan receptor family proteins. The aim of this study was to determine the intracellular synthesis profile of melatonin in Saccharomyces cerevisiae and to identify the proteins that may interact with this molecule in yeast cells. Melatonin from fermentation samples was analyzed by liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 51 publications
(71 reference statements)
4
15
0
Order By: Relevance
“…A screening of Saccharomyces and non-Saccharomyces strains revealed that melatonin synthesis took place at the end of the exponential growth phase, and its presence during fermentation followed a zigzag pattern that appeared and disappeared (59,78). These results were also corroborated during grape must fermentation (79).…”
Section: Physiological Role Of Melatonin In Yeastmentioning
confidence: 76%
“…A screening of Saccharomyces and non-Saccharomyces strains revealed that melatonin synthesis took place at the end of the exponential growth phase, and its presence during fermentation followed a zigzag pattern that appeared and disappeared (59,78). These results were also corroborated during grape must fermentation (79).…”
Section: Physiological Role Of Melatonin In Yeastmentioning
confidence: 76%
“…Indeed, it has been reported that hypoxia induces the formation of foci containing glycolytic enzymes, which increases the incorporation of carbon into pyruvate and oxaloacetate [ 91 ]. Recently, melatonin has been shown to bind a complex of glycolytic enzymes [ 17 ], and this binding would be related to yeast fermentative capacity [ 18 ]. Several glycolytic genes found in this complex, such as PYC2 and TDH3 , were upregulated by melatonin in non-stressed cells ( Figure 1 B,E, Dataset S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…For intracellular melatonin quantification, 10 8 cells were harvested from the samples at 0 h (just before stress induction) and 1 h after the stress induction by centrifugation at 4700× g for 15 min. Intracellular melatonin quantification was performed as previously described by Morcillo-Parra et al [ 17 ]. In brief, melatonin was extracted by adapting the boiling buffered ethanol method described by Gonzalez et al [ 28 ] and quantified by liquid chromatography mass spectrometry using a liquid chromatograph coupled to a triple quadrupole mass spectrometer (LC-MS/MS Agilent G6410A; Agilent Technologies Inc., Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it was found that glycolytic proteins may have interaction with intracellular MEL in S . cerevisiae and thereby restrict the recovery of this molecule during the first 24 h of lag phase from fermented products (Morcillo‐Parra, Valera, Beltran, Mas, & Torija, 2019). However, after this time the MEL that has been produced intracellularly in the lag phase begins to be exported to extracellular media during the stationary phase.…”
Section: Biosynthesis Of Melatonin Under Fermentation Conditionsmentioning
confidence: 99%